Growth and carcass mineralisation of Pacific whiteleg shrimp Penaeus vannamei Boone 1931 in response to water salinity - Jannathulla, R.; Dayal, J. Syama; Chitra, V.; Ambasankar, K.; Muralidhar, M. (Indian Journal of Fisheries, 2017)
The effect of water salinity (3, 10, 20, 30, 40, 50 and 60‰) on growth and proximate as well as mineral composition of Pacific whiteleg shrimp Penaeus vannamei was evaluated in a 45-day indoor trial. Significantly higher (p